Natural Tourism Empowerment Construction through Brand Strategy based Online Marketplace to Accelerate the Development and Enhancement of Industrial Competitiveness 4.0 in Undeveloped Areas of the Coast of East Java - SOEHARDJOEPRI, SOEHARDJOEPRI; BALAFIF, Mamak; WIDYASTUTY, Anak Agung Sagung Alit; WIDIANA, Muslichah Erma (Journal of Environmental Management and Tourism; Vol 11 No 8 (2020): JEMT Volume XI Issue 8(48) Winter 2020, 2021)
The aim of this research was to find a form of construction of natural tourism empowerment through a brand strategy based online marketplace to accelerate development and enhance the competitiveness of industry 4.0 in undeveloped areas of the coastal areas of East Java. The research sites were in 2 regency, namely Bangkalan Regency and Situbondo Regency. The analysis technique used Triangulation analysis. The conclusion of this research is that from a geographical point of view, Situbondo Regency has the potential of large and prospective natural resources to be developed as a driving force for social economic growth. Situbondo Regency has a large sea area and a fairly dense forest area. This is a very large asset of Situbondo Regency as an economic source to encourage the development of a populist economy. Online Marketplaces that are often used are Instagram, Facebook and Websites. The Situbondo Regency Brand Strategy: Situbondo Regency as a Fisherman Village and the Tourism Gateway for Baluran Forest. Bangkalan is the entrance to Madura Island that can be used as a brand strategy. The Madura Gate, the Greatness of Madura, the Future of Madura, can be taken into consideration in the preparation of City Branding.